PERTANGGUNGJAWABAN INDIVIDU ATAS GANTI RUGI DISGORGEMENT YANG MELIBATKAN EMITEN - Nikmah Mentari (Arena Hukum, 2020)
AbstractThe Financial Services Authority (OJK) launched a discourse by issuing an RPOJK regarding the Disgorgement and Disgorgement Fund. The parties that can be subject to disgorgement are the perpetrators of the violations themselves, including the Issuer as a public limited liability company. However, if the Issuer commits a violation, it is reasonable for the order to be addressed to the in persona (private individual), considering the Issuer is an artificial person who has no will and cannot have a will without the party carrying out behind the scenes. Directors, Commissioners and major shareholders (controllers) are parties who are allowed to commit violations and at the same time enjoy illegal profits from the violation. However, affiliated parties may commit violations involving the Issuer, so if there is an illegal profit, those who enjoy the benefit should be obliged to compensate the disgorgement. The issuer as a public limited liability company has also received administrative sanctions by both the OJK and the stock exchange. It is very unfair for the Issuer to be responsible for paying disgorgement compensation.AbstrakOtoritas Jasa Keuangan (OJK) meluncurkan wacana dengan mengeluarkan RPOJK tentang Disgorgement dan Disgorgement Fund. Para pihak yang dapat dikenakan disgorgement adalah pelaku pelanggaran itu sendiri, termasuk Emiten selaku perseroan terbatas terbuka. Akan tetapi, apabila Emiten melakukan pelanggaran, sewajarnya perintah tersebut ditujukan pada pelaku in persona (individu pribadi), mengingat Emiten sebagai artificial person yang tidak memiliki kehendak dan tidak dapat berkehendak tanpa pihak yang menjalankan di balik layar. Direksi, Komisaris dan pemegang saham utama (pengendali) merupakan pihak yang mungkin melakukan pelanggaran sekaligus menikmati keuntungan ilegal dari pelanggaran tersebut. Namun, pihak terafiliasi mungkin melakukan pelanggaran yang melibatkan Emiten, sehingga apabila terdapat keuntugan ilegal, seharusnya yang menikmati keuntungan tersebut yang diwajibkan mengganti rugi disgorgement. Emiten sebagai perseroan terbatas terbuka juga telah menerima sanksi administratif baik oleh OJK maupun bursa efek. Sangat tidak adil bagi Emiten bila harus bertanggung jawab membayar ganti rugi disgorgement.Â